Pharmacology of Kappa Opioid Receptors: Novel Assays and Ligands - Sturaro, Chiara; Malfacini, Davide; Argentieri, Michela; Djeujo, Francine M.; Marzola, Erika; Albanese, Valentina; Ruzza, Chiara; Guerrini, Remo; Calo’, Girolamo; Molinari, Paola (Frontiers in Pharmacology, 2022)
The present study investigated the in vitro pharmacology of the human kappa opioid receptor using multiple assays, including calcium mobilization in cells expressing chimeric G proteins, the dynamic mass redistribution (DMR) label-free assay, and a bioluminescence resonance energy transfer (BRET) assay that allows measurement of receptor interaction with G protein and β-arrestin 2. In all assays, dynorphin A, U-69,593, and [D-Pro10]dyn(1-11)-NH2 behaved as full agonists with the following rank order of potency [D-Pro10]dyn(1-11)-NH2 > dynorphin A > U-69,593. [Dmt1,Tic2]dyn(1-11)-NH2 behaved as a moderate potency pure antagonist in the kappa-β-arrestin 2 interaction assay and as low efficacy partial agonist in the other assays. Norbinaltorphimine acted as a highly potent and pure antagonist in all assays except kappa-G protein interaction, where it displayed efficacy as an inverse agonist. The pharmacological actions of novel kappa ligands, namely the dynorphin A tetrameric derivative PWT2-Dyn A and of the palmitoylated derivative Dyn A-palmitic, were also investigated. PWT2-Dyn A and Dyn A-palmitic mimicked dynorphin A effects in all assays showing similar maximal effects but 3-10 fold lower potency. In conclusion, in the present study, multiple in vitro assays for the kappa receptor have been set up and pharmacologically validated. In addition, PWT2-Dyn A and Dyn A-palmitic were characterized as potent full agonists; these compounds are worthy of further investigation in vivo for those conditions in which the activation of the kappa opioid receptor elicits beneficial effects e.g. pain and pruritus.